2021
DOI: 10.3390/ijms22147739
|View full text |Cite
|
Sign up to set email alerts
|

The bZIP Transcription Factor HapX Is Post-Translationally Regulated to Control Iron Homeostasis in Aspergillus fumigatus

Abstract: The airborne fungus Aspergillus fumigatus causes opportunistic infections in humans with high mortality rates in immunocompromised patients. Previous work established that the bZIP transcription factor HapX is essential for virulence via adaptation to iron limitation by repressing iron-consuming pathways and activating iron acquisition mechanisms. Moreover, HapX was shown to be essential for transcriptional activation of vacuolar iron storage and iron-dependent pathways in response to iron availability. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
6
1
Order By: Relevance
“…Furthermore, the inability of the Fo mac1 Δ mutant to grow in -Cu conditions confirms that the function of Mac1 is highly conserved across different fungi, which is in line with a previous study showing that the mac1 gene from A. fumigatus can functionally complement a mac1 Δ mutant of S. cerevisiae (Park et al, 2017). By contrast, we found that the post-translational regulation of Mac1 activity in Fo differs from that reported in other fungi where inactivation under copper sufficiency occurs mainly by protein degradation and/or cytoplasmic retention, analogous to what has been reported for the iron-responsive transcription factor HapX(Lopez-Berges et al, 2021). In S. cerevisiae , Mac1 is stable at low copper concentrations but rapidly degraded at concentrations above 10 µM CuSO 4(Zhu et al., 1998) .…”
Section: Discussioncontrasting
confidence: 65%
“…Furthermore, the inability of the Fo mac1 Δ mutant to grow in -Cu conditions confirms that the function of Mac1 is highly conserved across different fungi, which is in line with a previous study showing that the mac1 gene from A. fumigatus can functionally complement a mac1 Δ mutant of S. cerevisiae (Park et al, 2017). By contrast, we found that the post-translational regulation of Mac1 activity in Fo differs from that reported in other fungi where inactivation under copper sufficiency occurs mainly by protein degradation and/or cytoplasmic retention, analogous to what has been reported for the iron-responsive transcription factor HapX(Lopez-Berges et al, 2021). In S. cerevisiae , Mac1 is stable at low copper concentrations but rapidly degraded at concentrations above 10 µM CuSO 4(Zhu et al., 1998) .…”
Section: Discussioncontrasting
confidence: 65%
“…Initially, we analyzed each promoter separately, to better establish the optimal conditions for their induction or repression. PxylP has been widely used in A. fumigatus ( 38 , 41 44 ), and the general conditions to obtain a high level of expression were set to 1% glucose and 1% xylose in minimal medium, while glucose alone would be suitable to efficiently downregulate PxylP -driven gene expression. We conducted a titration analysis using 1% glucose and xylose in a concentration range from 0% to 3%, and we confirmed, as previously described ( 38 ), that a concentration as low as 0.09% xylose was sufficient for induction ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the latter are known to be iron regulated at the TL level ( 6 , 26 , 27 ), the control of TLs of the RIA and SIA genes during germination appears to be mediated by developmental regulators rather than by the iron-sensing transcription factors. However, HapX was recently shown to be subject to posttranslational modification ( 34 ), and therefore, it cannot be excluded that SIA and RIA are influenced by posttranslational modification of HapX and/or SreA. Moreover, the significantly higher TLs of genes involved in biosynthesis and uptake of FC in conidia and early germination ( sit1 , sidC , sidL ) than genes involved in biosynthesis and uptake of TAFC ( mirB , sidG ) indicated a role of biosynthesis and uptake of FC.…”
Section: Resultsmentioning
confidence: 99%